A 5-Year Update and Comparison of Factors Related to the Sex Diversity of Orthopaedic Residency Programs in the United States. Issue 1 (7th January 2023) - Julian, Kaitlyn R.; Anand, Malini; Sobel, Andrew D.; Mulcahey, Mary K.; Wong, Stephanie E.
Abstract : Introduction: Female physicians have been historically underrepresented in orthopaedic surgery residencies. The purpose of this study was to determine whether sex diversity among orthopaedic residency programs and faculty is associated with an increased number of female residents matriculating into that program. In addition, we sought to analyze female resident matriculation trends in the past 5 years. Methods: The American Medical Association Fellowship and Residency Electronic Interactive Database was used to identify all allopathic orthopaedic surgery residency programs during the 2021 to 2022 academic year. The number of female residents and interns; the number of female faculty, professors, and associate professors; and the number of women in leadership positions were compared with data from the academic year 2016 to 2017. Continuous data were analyzed with independent t-tests, and significance was set at p < 0.05. Results: A total of 696 female residents (19.2%) were identified from 3, 624 orthopaedic residents, an increase from 13.5% in 2016. Programs in the top quartile of female residents had 3 times the number of female residents per program when compared to other quartiles and almost double the number of female interns per program. Programs in the top quartile of female residents had a significantly greater number of female faculty per program than the lower quartiles; 5.76 vs. 4.18. Compared with 2016 to 2017, there were significant increases in female faculty per program from 2.77 to 4.54 along with female full professors from 0.274 to 0.694. These increases contribute to the overall growth in the number of women in leadership positions per program over the past 5 years to 1.01 from 0.35 (p < 0.001). Conclusion: In the past 5 years, the percentage of female residents has increased from 13.5% to 19.2%. Furthermore, women make up 22.1% of interns. Orthopaedic surgery residency programs with higher percentages of female faculty had higher numbers of female residents. By encouraging programs to promote female representation within leadership and residents, we may continue to see the gap in orthopaedic sex diversity close. Level of Evidence: III.